2018
DOI: 10.1093/botlinnean/boy051
|View full text |Cite
|
Sign up to set email alerts
|

Towards integrative taxonomy in Neotropical botany: disentangling the Pagamea guianensis species complex (Rubiaceae)

Abstract: Species complexes are common in the Neotropical flora, and the Pagamea guianensis complex is one of the most widespread groups of species in the Amazonian white-sand flora. Previous analyses suggested the occurrence of ten species in this group, but species limits remained unclear due to poor sampling, morphological overlap and low molecular variation. Here we present the most comprehensive population and molecular sampling across the geographical distribution of the P. guianensis complex to date in order to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 65 publications
4
47
0
Order By: Relevance
“…Recent studies of two diverse Amazonian genera, Eschweilera (Durgante & al., ) and Protium (Lang & al., ), showed that NIR spectra could accurately discriminate distinct species with over 96% success. Regarding closely related plant groups, this technology has been effective to discriminate cryptic species within Pagamea (Rubiaceae) (Prata & al., ). In addition to the morphological and phylogenetic results, the NIR data indicate that P. cordatum and P. heptaphyllum have distinct spectral signatures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recent studies of two diverse Amazonian genera, Eschweilera (Durgante & al., ) and Protium (Lang & al., ), showed that NIR spectra could accurately discriminate distinct species with over 96% success. Regarding closely related plant groups, this technology has been effective to discriminate cryptic species within Pagamea (Rubiaceae) (Prata & al., ). In addition to the morphological and phylogenetic results, the NIR data indicate that P. cordatum and P. heptaphyllum have distinct spectral signatures.…”
Section: Discussionmentioning
confidence: 97%
“…The spectrometer generates an absorbance response that is a function of the chemical composition and internal anatomy of leaves, which has been shown to be conserved within populations of the same species in a large study with more than 1000 tropical tree species (Asner & al., ). Analyzing the spectral signatures of near‐infrared reflectance of herbarium specimens can allow the discrimination of morphotypes even when there is a high phenotypic overlap among samples, and informative vegetative and reproductive traits are unknown (Durgante & al., ; Prata & al., ).…”
Section: Introductionmentioning
confidence: 97%
“…Our best results show that the best models and validations can, on average, correctly predict the identification of species 96.7 % of the time when using all wavelengths to construct the models, which is comparable to previously published taxonomic works. Prata et al (2018) demonstrated for the first time that near-infrared spectroscopy on leaves of subspecies of the Pagamea guianensis complex can discriminate taxa with high precision. Fan et al (2010) tested and proved the reliability of the technique at discriminating Ephedra plants from different habitats and collection seasons, while Lang et al (2017) showed the effectiveness of the technique at discriminating species, genera, and families of tree species from eighteen different angiosperm families.…”
Section: Discussionmentioning
confidence: 99%
“…Research using near-infrared spectroscopy to discriminate plant species is gaining more and more attention in plant taxonomy, especially for angiosperms (Durgante et al 2013; Kim et al 2004; Krajšek et al 2008; Lang et al 2017). The tool has been shown to be more practical and accurate than genetic or morphological methods (Castillo et al 2008), is capable of consistently discriminating phylogenetic relationships of flowering plant species (Kim et al 2004), and has been used in different works to aid in species circumscription and identification of several plant groups (Damasco et al 2019; Durgante et al 2013; Lang et al 2017; Prata et al 2018; Shen et al 2020). However, the technique has not been tested to identify other groups of embryophytes, such as ferns and lycophytes, or bryophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Species delimitation methods are also catching up to the statistical rigor of phylogenetics, with model-based methods (e.g., Zapata & Jiménez, 2012; Yang, 2015) Lagomarsino & Frost Taxonomy in the Study of Neotropical Biodiversity frequently applied instead of, or in addition to, a taxonomic expert's gestalt. This has resulted in a blooming subfield known as "integrative taxonomy" (Schlick-Steiner et al, 2010;Fujita et al, 2012;Prata et al, 2018), which reduces subjectivity and facilitates stability in classification schemes. As a result, descriptive taxonomy is becoming a more rigorous discipline (Sangster & Luksenberg, 2015).…”
Section: Challenges To Increasing the Reach Of Floristics And Taxonomymentioning
confidence: 99%